2013
DOI: 10.11604/pamj.2013.15.35.2198
|View full text |Cite
|
Sign up to set email alerts
|

Loss of HIV-infected patients on potent antiretroviral therapy programs in Togo: risk factors and the fate of these patients

Abstract: IntroductionNational programs are facing challenges of loss to follow-up of people living with HIV/AIDS (PLWHA) on antiretroviral therapy (ART). We sought to identify risk factors associated with early loss to follow-up among HIV-infected patients on ART in Togo and the outcome of such patients.MethodsThis was a retrospective cross-sectional study using medical records of all patients older than age 15 years enrolled at 28 treatment centers who were on ART programs and who were lost to follow-up from 2008 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
4
14
2
1
Order By: Relevance
“… 17 , 21 , 28 30 The association between advanced disease conditions at ART initiation (low CD4, AIDS stage) and higher probability of death or being LTFU has been largely observed. 10 , 11 , 15 17 , 31 36 This seems to be the most important factor associated with LTFU in the oldest group.…”
Section: Discussionmentioning
confidence: 94%
“… 17 , 21 , 28 30 The association between advanced disease conditions at ART initiation (low CD4, AIDS stage) and higher probability of death or being LTFU has been largely observed. 10 , 11 , 15 17 , 31 36 This seems to be the most important factor associated with LTFU in the oldest group.…”
Section: Discussionmentioning
confidence: 94%
“…We excluded 1589 items for the reasons detailed in Figure . Thirty articles met inclusion criteria . Two studies reported results for children and adults separately.…”
Section: Resultsmentioning
confidence: 99%
“…One study in Togo including 16,617 HIV-positive patients showed that 7% were lost to follow-up after initiation of treatment after 6 months. In another study, of 13,726 participants whose phone number was listed, 80% were not reachable on the known phone number [ 6 ]. In a study in Cote d’Ivoire of patients on antiretroviral therapy (ART), an attempt was made to trace approximately 7000 patients through telephone calls who were lost to follow-up.…”
Section: Introductionmentioning
confidence: 99%